The Flexing Phenomenon on Social Media Is Between Educating and Showing Off in Criminal Law Aspects - Merry Lenda Kumajas; Henry N. Lumenta; Paulus Robert Tuerah; Hendrasari Rawung; Romi Mesra (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2024)
This study aims to investigate the flexing phenomenon on social media, exploring its position between financial education and ostentatious displays of wealth, with a focus on its implications in criminal law aspects in Indonesia. The research employed a qualitative methodology, utilizing interviews with key stakeholders, focus group discussions, analysis of social media content, and a comprehensive literature review. Additionally, the study incorporated comparative analysis with other Southeast Asian countries to provide regional context. The results reveal a complex interplay of social, legal, and educational factors surrounding the flexing phenomenon. Key findings include: (1) a significant divergence in perceptions of flexing among different stakeholders, with influencers viewing it as inspirational while legal experts express concerns about potential legal scrutiny; (2) the effectiveness of flexing as an educational tool when balancing success stories with practical financial advice; (3) a notable knowledge gap among social media users regarding the legal implications of their online behavior; (4) growing concerns about the use of social media evidence in financial crime investigations; (5) the emergence of "aspirational flexing" among younger users, raising ethical and potential legal issues; and (6) a shift in public perceptions of wealth and success due to constant exposure to luxury displays on social media. The study concludes that while flexing can serve as a powerful educational tool, it also presents significant legal risks and societal challenges that require a balanced approach to address effectively